Kontribusi Gender terhadap Produktivitas Usahatani Padi Gogo di Kecamatan Wolasi Kabupaten Konawe Selatan - Ita Dyan Hari Purnamasari; Weka Widayati; Sitti Aidha Adha Taridala (Universitas Halu Oleo, 2020)
This study aims to determine and analyze the relationship between gender contributions to the productivity of upland rice farming in Wolasi District, Konawe Selatan Regency. The study was conducted from April to August 2019. The study population was all upland rice farmers who received liquid organic fertilizer assistance. The sample was taken by using simple random sampling method. The number of samples was 38 farmers. The data observed were the amount of work day for male and female farmers, and the productivity of upland rice farming. Data analysis was performed using the Pearson Correlation test. The results of the study show that the relationship between gender contribution and upland rice farming productivity is very weak, which means that the quality of the work done by men is not different from that done by women.Keywords: gender contribution; productivity; upland rice farming